Adaptation of precision agriculture systems to conditions of labor shortages in agriculture - Olkhovsky, Volodymyr (Актуальні питання економічних наук, 2025)
The study’s relevance is driven by the increasing shortage of human resources in agriculture, shaped by demographic changes, labor migration, shifts in the age structure of the agricultural workforce, and growing qualification requirements. Under these conditions, traditional agricultural production models are losing effectiveness, underscoring the need for scientifically grounded adaptation of precision agriculture systems to compensate for labor constraints and enhance the stability and controllability of production processes. The purpose of the article is to substantiate directions and practical instruments for adapting precision agriculture systems to conditions of labour shortages in agriculture to increase the efficiency, autonomy, and resilience of agroproduction processes. Methods. The study applies a systemic and structural-functional approach, comparative analysis, and analytical generalization. These methods enabled examining the impact of labour shortages on the organization of agricultural production, assessing the functional potential of precision agriculture systems to reduce labour intensity, and generalizing approaches to adapting digital and automated agrotechnologies with limited personnel involvement. Results. It has been established that labour shortages in agriculture are systemic and affect both the execution of technological operations and the quality of managerial decision-making. It has been proven that precision agriculture systems can compensate for human resource constraints through process autonomy, algorithmisation of management decisions, and standardization of agrotechnological operations. Key scientific and practical problems of adaptation and implementation have been identified, including managerial inertia, mismatch between technological complexity and staff competencies, fragmentation of digital solutions, technological risks, and difficulties in substantiating economic efficiency. Conclusions. It has been substantiated that effective use of precision agriculture systems under labour shortages is achievable only through the combination of technological autonomy with organizational transformation of agricultural enterprises and a clear redistribution of functions between human operators and technological systems. The expediency of transitioning from fragmented digital implementation to a systemic adaptation of agrotechnologies has been proven. Prospects for further research include developing quantitative models to assess the impact of autonomous agrotechnologies on labour productivity and the economic sustainability of agricultural enterprises, determining optimal levels of technological autonomy, and analyzing the long-term organizational consequences of digital transformation in the agricultural sector.